Increasing evidence that bats actively forage at wind turbines - Cecily F. Foo; Victoria J. Bennett; Amanda M. Hale; Jennifer M. Korstian; Alison J. Schildt; Dean A. Williams (PeerJ, 2017)
Although the ultimate causes of high bat fatalities at wind farms are not well understood, several lines of evidence suggest that bats are attracted to wind turbines. One hypothesis is that bats would be attracted to turbines as a foraging resource if the insects that bats prey upon are commonly present on and around the turbine towers. To investigate the role that foraging activity may play in bat fatalities, we conducted a series of surveys at a wind farm in the southern Great Plains of the US from 2011–2016. From acoustic monitoring we recorded foraging activity, including feeding buzzes indicative of prey capture, in the immediate vicinity of turbine towers from all six bat species known to be present at this site. From insect surveys we found Lepidoptera, Coleoptera, and Orthoptera in consistently high proportions over several years suggesting that food resources for bats were consistently available at wind turbines. We used DNA barcoding techniques to assess bat diet composition of (1) stomach contents from 47 eastern red bat (Lasiurus borealis) and 24 hoary bat (Lasiurus cinereus) carcasses collected in fatality searches, and (2) fecal pellets from 23 eastern red bats that were found on turbine towers, transformers, and tower doors. We found that the majority of the eastern red bat and hoary bat stomachs, the two bat species most commonly found in fatality searches at this site, were full or partially full, indicating that the bats were likely killed while foraging. Although Lepidoptera and Orthoptera dominated the diets of these two bat species, both consumed a range of prey items with individual bats having from one to six insect species in their stomachs at the time of death. The prey items identified from eastern red bat fecal pellets showed similar results. A comparison of the turbine insect community to the diet analysis results revealed that the most abundant insects at wind turbines, including terrestrial insects such as crickets and several important crop pests, were also commonly eaten by eastern red and hoary bats. Collectively, these findings suggest that bats are actively foraging around wind turbines and that measures to minimize bat fatalities should be broadly implemented at wind facilities.